"Blinking" silica nanoparticles for optical super resolution imaging of cancer cells. Issue 77 (17th October 2017) - Li, Jia; Zong, Shenfei; Wang, Zhuyuan; Cui, Yiping
Abstract : A strategy to fabricate blinking silica nanoparticles is presented, which can be used in single molecule localization imaging. Abstract : Fluorophores for single molecule localization microscopy (SMLM) must exhibit continuous signal fluctuations ( i.e. blinking). Here, we present a strategy to make silica nanoparticles (NPs) blink using Alexa Fluor 647 (A647), an organic dye widely used in SMLM. We find that encapsulating A647 inside the silica NPs produces non-blinking silica NPs, while decorating A647 onto the outer surface of silica NPs generates blinking silica NPs. The morphology and fluorescence properties of the blinking silica NPs are studied. Besides, by attaching cancer specific antibodies, the blinking silica NPs can specifically target the cancer cells. Cells incorporated with the blinking silica NPs are imaged using confocal laser scanning microscopy and SMLM. With the optical super resolution imaging ability, this kind of cancer specific blinking silica NPs can have a great potential in detailed investigation of the interaction between cancer cells and NPs.